2015
DOI: 10.1039/c5cc03537f
|View full text |Cite
|
Sign up to set email alerts
|

Rapid synthesis of ultrathin, defect-free ZIF-8 membranes via chemical vapour modification of a polymeric support

Abstract: Ultrathin ZIF-8 membranes with a thickness of around 200 nm were prepared by chemical vapour modification of surface chemistry and nanopores of an asymmetric bromomethylated poly(2,6-dimethyl-1,4-phenylene oxide) (BPPO) substrate. The resulting ZIF-8 membranes exhibited exceptional H2 permeance as high as 2.05 × 10(-6) mol m(-2) s(-1) Pa(-1) with high H2/N2 and H2/CO2 selectivities (9.7 and 12.8, respectively).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 34 publications
4
78
0
Order By: Relevance
“…Notably, in no cases was surface modification of PIM-1 necessary to adhere the ZnO nanocrystals or ZIF films, where in previous work, amine functionalization of the polymer was needed to promote heterogeneous nucleation and adhesion of the ZIF. 27 Cross-sectional and top-down SEM were used to study the resultant film morphology. Contrast differences between residual ZnO nanocrystals and the overlying ZIF made each phase readily distinguishable.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Notably, in no cases was surface modification of PIM-1 necessary to adhere the ZnO nanocrystals or ZIF films, where in previous work, amine functionalization of the polymer was needed to promote heterogeneous nucleation and adhesion of the ZIF. 27 Cross-sectional and top-down SEM were used to study the resultant film morphology. Contrast differences between residual ZnO nanocrystals and the overlying ZIF made each phase readily distinguishable.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the strong adhesion between MOF layer and polymer substrates is very important for the stability and performance of MOF membranes [29]. Chemical modification, usually carried out by fabrication of polar group including the -COOH and -NH 2 on the surface of the substrates, can increase the heterogeneous nucleation and then enhance adhesion and improve growth of MOF layers greatly [21,[30][31][32][33][34][35][36]. PVDF, a stable polymer, has been widely used in membrane fabrication and may be a useful choice besides PAN.…”
Section: Introductionmentioning
confidence: 99%
“…However, an insufficient number of heterogeneous nucleation sites on the bare support and poor adhesion between the MOF layer and the substrate, may result in defective MOF films with inter-crystalline gaps between particles. Surface functionalization of substrates can effectively solve this issue by producing surface attached functional groups that act as anchors to ligands or metal ions for promoting heterogeneous nucleation and MOF film growth [30]. Hou et al [23,31] reported zeolitic imidazolate framework-8 (ZIF-8) thin films on indium tin oxide (ITO) supports modified with 3-aminopropyltriethoxysilane (APTES) as a covalent linker between ZIF-8 crystals and ITO supports.…”
Section: Introductionmentioning
confidence: 99%
“…Permeation tests of ZIF-8/polysulfone show high hydrogen separation performance, confirming the molecular sieving effect of ZIF-8. Recently, Shamsaei et al [30] have prepared an ultrathin ZIF-8 membrane on the surface of bromomethylated poly(2,6-dimethyl-1,4-phenylene oxide) (BPPO) substrate after being modified with ethylene diamine (ED). The resulting ZIF-8/ED-modified BPPO membranes exhibited a significantly higher H 2 permeance compared to other gases.…”
Section: Introductionmentioning
confidence: 99%